Essential core competencies for scope of practice of paediatric oncology nurses in Latin America: a scoping review protocol - Luís Carlos Lopes-Júnior; Regina Aparecida Garcia Lima; Soad Fuentes-Alabi; Edmara Bazoni Soares Maia; Karina de Cássia Braga Ribeiro; Courtney E Sullivan; Monnie Abraham; Lorena Segovia Weber; Liliana Vásquez Ponce (BMJ Open)
Introduction Nurses comprise the largest group of health workers globally and are essential to the provision of care necessary for delivering curative therapy to children with cancer. In high-income countries, previous studies of the nurse workforce have shown an association between patient morbidity and mortality and nursing-related factors such as staffing, education and the nursing practice environment. There is currently limited evidence available to define the scope of essential core competencies for paediatric oncology nursing (PON) practice internationally and specifically in Latin America. Clearly defined essential core competencies contribute to establishing nurses’ scope of practice within clinical practice, education and research settings. Here, we aimed to map and synthesise the available evidence on the scope of PON practices in the context of clinical practice, educational training and research settings in Latin America.Methods A scoping review (ScR) protocol is reported, adhering to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols statement and guided by The Joanna Briggs Institute. MEDLINE/PubMed, Cochrane Library, Embase, CINAHL, Web of Science, Scopus, Science Direct and Latin American and Caribbean Health Sciences Literature, plus additional sources: The ProQuest Dissertation & Theses Global, The British Library, Google Scholar, medRXiv, ClinicalTrials.gov and WHO-ICTRP will be searched. No date or language restrictions will be employed. Two independent researchers will conduct all the steps of this ScR. The findings will be presented through tables, charts, narrative summaries and assessed based on the outcomes. The search strategy will be updated in May 2022. The expected completion date for this ScR is November 2022.Ethics/dissemination This protocol does not require ethical approval. The dissemination plans comprise peer-reviewed publication and conference presentations, to be shared with International Oncology Societies/International Nursing Societies and advisory groups to inform discussions on future research. We expect that our results will be of interest to nurse professionals, especially, PON and nurse scholars concerned with this particular issue.